A Case of Osteochondroma in a Cat's Ear - Eren Polat; Burak Karabulut; Elif Ekinci (Revista MVZ Cordoba)
In this case report, we aimed to share the clinical and histopathological examination and treatment process of a 6-month-old hybrid cat brought with the complaint of swelling in the medial part of the right auricle. In clinical examination, it was determined that the mass had a hard and irregular surface structure. As a result of the clinical examination, it was decided to completely extirpate the mass and send it to the pathology department. The mass was widely separated from the surrounding tissues and extirpated with the help of cautery. Microscopic examination of the mass revealed that there were chondrocytes among the dense bone cell accumulations and that they formed islands in some areas. As a result of histopathological examinations, it was determined that the suspicious mass was osteochondroma. During the postoperative examinations, it was determined that there was no recurrence or complication in the patient. As a result, it was concluded that this presentation will contribute to the literature since osteochondroma masses are rare in the ear region.